PENGARUH DEMOSI, MUTASI DAN PROMOSI JABATAN TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN PINRANG - Kadir, Abdul; Sampara, Nirwana; Bachtiar, Yusran (Universitas Muhammadiyah Parepare, 2021)
This study should determine and analyze the impact of degradation, transfer and promotion, both at the same time and partly, the influence on the implementation of the regional secretary employee in Pinrreg Regency, South Sulawesi. The data in this study uses, whose primary data from the Secretariat's Secretariat of the Pinrag district of a secondary data request list and instruments in this study will be measured using a label scale. The method used is the multiple linear regression analysis used to determine, and both analyze at the same time and partly between the independent variables which affects the dependent variable in this case, which influences the dependent variable in this case, is the implementation of regional Secretary Employees in Pinrang Regency, South Sulawesi. The results of this study. With regard to the results of this study, there is no partial impact of degradation about performance, as degradation is rarely treated as a sanction of employees, mutations have a partial significant impact on performance, this is because mutations are usually carried out, While promotions are not used not clearly its effect on performance during promotions this is the result of the bore promotion with a low program is given by the agency, of course, has an impact on the low performance of the employees, while the test results show simultaneously that the three Variables, namely, the variables, mutation and promotion of position, influence the performance of employees at the Pinrreg district counselor office